Razão, honestidade e sensibilidade: novas concepções sobre masculinidade(s) - Vicente, Daniel Domith (2005)
The studies on masculinity are growing on numbers in several areas of human sciences, and even natural sciences, mainly when focused on health. This interest in men, however, is recent, if compared to gender studies, which exists for decades, with an almost exclusive focus on women. This study on masculinities has had the objective of verifying the conception of masculinity of young men and women of Vitória, E.S. Also, we tried to verify if and how those conceptions articulate with some of the characteristics of liberalism and of the western capitalist way of production, and also how masculinity models can help to strength those same characteristics and be strengthened by them. The data were collected through semi-structured interviews with 20 participants, 10 men and 10 women, aged between 23 and 30 years old, all of them had with college degree or were in college. The interviews focused elements that compose the most present masculine models in western cultures, such as the active character of men, reason, sexual potency and the male function as the provider. The data were grouped in categories after the analysis of content had been made. Results indicated that the main characteristics of the participants conceptions were strength, intimately connected to the supposed active character of man; and honesty. Inexorable articulated, both, in spite of positive aspects are connected to reactionary and essentialists conceptions of masculine superiority. At the same time, traditional elements of masculinity like reason, the function as the provider and sexual potency, appear to be more flexible. The conclusion is that, indeed, various characteristics of western masculinity models articulate with practices of capitalist way of production, practices that many times are not healthy and leads to exploration and domination. Also is concluded that there is today a search of men and women for a greater equality in gender relations, even though that search is full of contradictions and still distant form satisfactory.